2016
DOI: 10.1080/08941939.2016.1232449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron-Based Gel on Radiation-Induced Dermatitis in Breast Cancer: A Double-Blind, Placebo-Controlled Trial

Abstract: Using the RTOG scoring system, we revealed that the application of a boron-based gel diminished RISR. The mechanism of action is unclear but may be related to antioxidant, wound healing, and thermal degradation effects of boron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
0
21
1
1
Order By: Relevance
“…Previous reports showed that radiation-induced skin reactions were observed in ~90% of breast cancer patients undergoing adjuvant postoperative radiotherapy. 21 , 22 In our data, the incidence is lower than the previous reports. It needs to be studied further if the skin color affects it.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Previous reports showed that radiation-induced skin reactions were observed in ~90% of breast cancer patients undergoing adjuvant postoperative radiotherapy. 21 , 22 In our data, the incidence is lower than the previous reports. It needs to be studied further if the skin color affects it.…”
Section: Discussioncontrasting
confidence: 75%
“… 8 There is no clear evidence indicating that a specific product can prevent or treat radiation-induced dermatitis. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In in-vitro and in-vivo studies performed by our group, sodium pentaborate has been shown to exert antiinflammatory effects through cell proliferation, cell migration, and growth factor expression pathways and to accelerate wound healing in different wound models [12,13]. In a prospective randomized clinical trial, we also revealed that sodium pentaborate gel prevents radiation induced dermatitis in breast cancer patients [14]. Adhesions cover a maximum of 1/3 of the model area Spontaneously separating adhesion 2…”
Section: Discussionmentioning
confidence: 82%
“…As boron is very similar to the carbon atom, many carbon-based molecules are the same as the boron-based molecules [1]. e wound healing benefits of some types of boron compounds, especially sodium pentaborate, have been previously documented [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Aysan ve ark.nın yaptığı çalışmada, meme kanseri hastalarında, borun radyasyona bağlı cilt reaksiyonlarını azalttığı gözlenmiş ve bu etkinin, borun antioksidan ve yara iyileştirici özelliğinden kaynaklanabileceği düşünülmüştür. 62…”
Section: Meme Kanseri̇unclassified